2021
DOI: 10.3389/fpubh.2021.559595
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility for Some Infectious Diseases in Patients With Diabetes: The Key Role of Glycemia

Abstract: Uncontrolled diabetes results in several metabolic alterations including hyperglycemia. Indeed, several preclinical and clinical studies have suggested that this condition may induce susceptibility and the development of more aggressive infectious diseases, especially those caused by some bacteria (including Chlamydophila pneumoniae, Haemophilus influenzae, and Streptococcus pneumoniae, among others) and viruses [such as coronavirus 2 (CoV2), Influenza A virus, Hepatitis B, etc.]. Although the precise mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 254 publications
2
50
0
3
Order By: Relevance
“…Therefore, hyperglycemia and the immune system can differentially impact the production of inflammatory mediators during microbial infection in diabetic individuals. These changes may not only actively participate in the inflammatory process of DM, accelerating the complications associated with the disease, but may also interfere with the host's defense against microbial infections [ 74 , 75 ].…”
Section: Main Findings and Discussionmentioning
confidence: 99%
“…Therefore, hyperglycemia and the immune system can differentially impact the production of inflammatory mediators during microbial infection in diabetic individuals. These changes may not only actively participate in the inflammatory process of DM, accelerating the complications associated with the disease, but may also interfere with the host's defense against microbial infections [ 74 , 75 ].…”
Section: Main Findings and Discussionmentioning
confidence: 99%
“…Insulin resistance lies at the key crossroads of metabolic and mitochondrial dysfunction, visceral fat, non-alcoholic fatty liver (NAFL), muscle exercise and weight loss resistance, subclinical inflammation, metabolic syndrome (MetS), overweight, and obesity, and is characterized by epigenetically driven accelerated aging, as Nannini et al [3] reported. Insulin resistance plays a key role in a reduced capability of the immune system to kill pathogens such as viruses and bacteria, as De Rosa et al [4] and Chávez-Reyes et al [5] reported. Vestergaard Jensen et al [6] reported insulin resistance as an important risk factor for community-acquired pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, diabetic patients are susceptible to infection and inflammation when exposed to pathogenic bacteria, and their infections cannot be easily cured since diabetic patients have defects in innate and adaptive immunity [65,66]. Furthermore, uncontrolled diabetes elevates the inflammatory response and oxidative stress, exacerbating infection [67].…”
Section: Glucose Metabolism and Gut Microbiotamentioning
confidence: 99%